Impact of perturbative, non-axisymmetric impurity fueling on Alcator C-Mod H-modes. (31st October 2017) - Reinke, M L; Lore, J D; Terry, J; Brunner, D; LaBombard, B; Lipschultz, B; Hubbard, A; Hughes, J W; Mumgaard, R; Pitts, R A
Abstract: Experiments on Alcator C-Mod have been performed to investigate the impact of toroidally localized impurity injection on H-mode exhaust scenarios. Results help to inform sub-divertor gas injector designs, in particular that of the ITER machine, for which this work was primarily undertaken. In repeated EDA H-modes, the amount of N2 injected into the private flux region was scanned up to levels which strongly impacted normalized energy confinement, H98, and led to an H/L back-transition. Repeated scans increased the toroidal peaking of the gas injection, reducing from five equally spaced locations to a single toroidal and poloidal injector. Results show the impact on the pedestal and core plasma is similar between all cases as long as the total gas injection rate is held constant. An influence on toroidally localized impurity spectroscopy is shown, demonstrating a complication in using such data in interpreting experiments and supporting boundary modeling in cases where there are localized extrinsic or intrinsic impurity sources. These results, along with prior work in this area on Alcator C-Mod, form a comprehensive set of L-mode and H-mode data to be used for validation of 3D boundary physics codes.